IMPLEMENTASI KEBIJAKAN PENGUKURAN KAPAL PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS III PANTOLOAN - Sunardi, Sunardi (Katalogis, 2017)
The research intends to find out the implementation of Ship Measurement at Harbormaster and Harbor Authority Class III Policy of Pantoloan. The research setting was conducted at the office of harbormaster and harbor authority class III of Pantoloan. This was a descriptive qualitative research with 95 people as the population consisted of 70 employees and 25 ship owners. Sample was selected using purposive sampling with 3 employees and 2 ship owners. Data collection was primary and secondary.The data were collected through observation, interview and documentation. Then, they were analyzed using qualitative approach with procedures namely data reduction, data display and drawing conclusion (verification). The results reveal that communications called transmission, clarity are consistent; resources which staff (ship measurement expert and facility) still look unwell, whereas disposition such as willingness, commitment, honesty, authority resources and bureaucratic structure covering Standard Operational Procedure and authority fragmentation already be good Therefore, based on the findings, it can be concluded that implementation of ship measurement is still less effective.